APPROACH TO TEAM CONFLICT RESOLUTION - Enes Huseinagić; Adnan Hodžić (Sport Scientific And Practical Aspects, 2025)
This work includes research of team conflict resolution styles in sports by basketball coaches. This research was conducted at the European Junior Basketball Championship B Division held from July 23 to August 2, 2009 in Sarajevo. Research tasks were created with the goal to establish styles for resolving team conflict by coaches in basketball, to determine dominating styles and with the help of a questionnaire to analyze opinion about correlation of the offered styles and their effectiveness. The questionnaire created by Kreitner and Kinicki (1998), has given answers on these hypotheses. Sample was comprised of 14 coaches from 24 basketball teams which took part in competition. The research was conducted through the questionnaire which covered five different conflict resolution styles: bonding, reconciling, imposing, avoiding and compromise. Coaches of tested teams who have dominating styles for resolving team conflicts caused by certain reasons, have shown that hypothesis relating to coach’s different adaptational styles of conflict resolution is completely confirmed.